Transbronchial lung cryobiopsy: prospective safety evaluation and 90-day mortality after a standardized examination protocol. (March 2022) - Hackner, Klaus; Stadler, Antonia; Schragel, Felix; Klamminger, Valerie; Ghanim, Bahil; Varga, Alexander; Errhalt, Peter
Background: Transbronchial lung cryobiopsy (TBLC) is a new method of bronchoscopic tissue sampling in patients with unclear diffuse parenchymal lung disease (DPLD). While not the gold standard, TBLC has a good diagnostic correlation with surgical lung biopsy, and retrospective analyses of peri-interventional complications and mortality are promising. However, prospective reports on 90-day mortality are lacking. Objectives: This study addresses morbidity and 30- and 90-day mortality in TBLC after a standardized protocol. Methods: In this prospective study, 75 patients with DPLD requiring tissue sampling were included. A standardized protocol (including prophylactic use of an endobronchial balloon, postinterventional observation, and minimum sampling requirements) was used in all patients. Adverse events (pneumothorax, bronchial bleeding, premature discontinuation, prolonged monitoring at ICU, and fatal outcome) and 30- and 90-day mortality rates were recorded. Results: A total of 308 cryobiopsies were performed in 75 patients. Peri- and postinterventional pneumothorax were observed in 20% (9.3% mild and 10.7% moderate with the necessity of chest drainage), and bronchial bleeding was found in 29.3% (22.7% moderate and 6.7% severe). Total lung capacity below normal value was associated with the risk of pneumothorax ( p = 0.009), and diffusion limitation for carbon monoxide below normal value was associated with the risk of bronchial bleeding ( p = 0.044). No fatal events were observed within 30 days, and the 90-day mortality rate was 1.3%, but not related to the procedure itself. Conclusion: As it gradually becomes the invasive procedure of choice in unclear DPLD, TBLC is a safe procedure with a low 30- and 90-day mortality. Trial registration ID: DRKS00026746 (German Clinical Trial Register)